The apocalypse codex - Stross, Charles (Stross, Charles. Laundry files novel., 2012)
"For outstanding heroism in the field (despite himself), computational demonologist Bob Howard is on the fast track for promotion to management within the Laundry, the supersecret British government agency tasked with defending the realm from occult threats. Assigned to External Assets, Bob discovers the company--unofficially--employs freelance agents to deal with sensitive situations that may embarrass Queen and Country. So when Ray Schiller--an American televangelist with the uncanny ability to miraculously heal the ill--becomes uncomfortably close to the Prime Minister, External Assets dispatches the brilliant, beautiful, and entirely unpredictable Persephone Hazard to infiltrate the Golden Promise Ministry and discover why the preacher is so interested in British politics. And it's Bob's job to make sure Persephone doesn't cause an international incident. But it's a supernatural incident that Bob needs to worry about--a global threat even the Laundry may be unable to clean up.."--